Mediation Role of Motivation on the Effect of Workload on Productivity in PT. Kurnia Luwuk Sejati - Mastia M Halimu; Mas’ud Said; Pardiman Pardiman (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to analyze the effect of workload on productivity, and motivation as a mediating variable between the two. This research was conducted on employees of PT. Kurnia Luwuk Sejati with a sample of 119 employees. Questionnaires were distributed directly to respondents accompanied by interviews. The data that has been successfully collected from the questionnaire is then analyzed using the Smartpls application with the SEM-PLS method. The results of this study indicate that workload significantly affects productivity, furthermore workload can also affect work motivation, work motivation also has a significant effect on productivity, then motivation successfully mediates the effect of workload on productivity.